Hydrophobicity Properties of Silica-Dimethylsilicone Oil-Stearic Acid Based Materials Applied as Waterproof Coating Materials - Joko Suryadi; Annisa Sri Rahmawati; Derina Maulinda; Ndaru Dwiyatmoko Mukti; Andhika Putera Utama; Haryadi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2026)
Geothermal solid waste is one of the byproduct materials from the geothermal energy process. The silica extracted from this solid waste can be utilized as a raw material for waterproof coatings. The waterproof or hydrophobic properties in this study have been studied with a formulation of silica, stearic acid, and dimethyl silicone oil. The technique of extracting silica from geothermal waste is carried out using the sol-gel method. Preparation of hydrophobic materials is carried out by mixing silica with stearic acid at a ratio of 1:3, 1:5, and 1:7 on a mass basis with the addition of dimethyl silicone oil as an emulsifier. The hydrophobic silica-dimethyl silicone oil-stearic acid materials were synthesized and characterized by functional group analysis using FTIR. The best hydrophobic properties are shown in a ratio of silica and stearic acid of 1:5. On a glass substrate, the silica-dimethyl silicone oil-stearic acid coating produced a contact angle of 110.2 °. On a fabric substrate, the coating exhibited a superhydrophobic phenomenon with a contact angle of 153.7 °.